SUMMATIVE ASSESSMENT PERFORMED BY ENGLISH TEACHER IN PANDEMIC ERA - Jihan Nur'ain Anjani (Journal of English Teaching and Linguistics Studies (JET Li), 2022)
Covid-19 pandemic changes people’s daily habits including educational activities. Schools have to conduct summative assessments online. Although in Indonesia online assessment is not that new, the teacher has to do a necessary assessment. This research aims to know how summative assessment is performed by high school English teachers in the pandemic era. This research is conducted at MAS Daarul Fataa. The participants in this research are 40 students, an English teacher, and a vice principal of curriculum of MAS Daarul Fataa. To gain the research data, documentation, questionnaires, and interviews are used as research instruments. According to the data analysis, it is found that students, teachers and schools have successfully carried out online exams. Google Form and What’s App are used as media to support online exam activities. The type of question used is multiple choice. The normal time to answer the question is 90 minutes, but for students whose signal was not good, they will get 120 minutes. Not only reading skills, students are also given questions in the form of vocabulary, phrases and grammar. All questions cover the material that has been given by the teacher and signal quality can affect how quickly students answer questions. Teacher says that the use of online media for exams is considered efficient. Students do not find any obstacles regarding technology, because they can use technology easily. Then students say that they take the exam according to their own abilities.